Corrigendum: Alignment of atomic inner-shells following alpha-decay-induced ionization - McConnell, Sean R.; Artemyev, Anton; Surzhykov, Andrey (Journal of physics. B, Atomic, molecular and optical physics, 2013)
The full text of this article is available in the PDF provided.